Juridical Review of Executorial Confiscation Power after the Constitutional Court Decision Number 18 / PUU-XVII / 2019 Against Act No. 42 of 1999 Regarding Fiduciary Guarantee - Lupita Randawi; Akhmad Khisni; Amin Purnawan (Jurnal Akta, 2020)
The purpose of this research is uTo: 1) To determine the legal strength of the executorial confiscation of a fiduciary guarantee certificate against a debtor who is in default (in default) and does not want to voluntarily hand over the goods that are the object of fiduciary security and 2) To know the procedure for implementing the execution of a fiduciary guarantee certificate for debtors who are in default (default) After the Constitutional Court Decision Number 18 / PUU-XVII / 2019 and (3) To find out what weaknesses and solutions can be obtained from the Constitutional Court Decision Number 18 / PUU-XVII / 2019. The data used in this study are primary data, secondary data, and tertiary data that can support the assessment, which are then analyzed using the normative juridical method. Based on the results of data analysis, it is concluded that: 1) based on the decision of the Constitutional Court Number 18 / PUU-XVII / 2019 seizure of the execution of the fiduciary guarantee by the creditor mustdone when there is an agreement regarding the default and the debtor's willingness to hand over the object that becomes the object of fiduciary. 2) If there is no agreement regarding default and the debtor does not voluntarily submit the object of guarantee, then the procedure for executing the fiduciary guarantee is carried out the same as the execution of a court decision which has permanent legal force.